Memory film, use thereof and method for manufacturing same
By using a memory film composed of acrylic and polyurethane on the skin, the problem of insufficient adhesion in the moist environment is solved, achieving uniform shrinkage of the skin and improving elasticity and wrinkles.
Patent Information
- Application Number
- CN202411868715.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-12-22
- Filing Date
- 2024-12-18
- Publication Date
- 2025-06-24
AI Technical Summary
The prior art is difficult to maintain adhesion in a humid environment, and it is difficult to uniformly transmit contraction force to the skin, affecting convenience and effect.
Using a memory film, the first layer consists of acrylic acid and polyurethane, the time after bonding to the skin can shrink at a memory ratio and be made by coating, drying and stretching processes.
It achieves the ability to maintain attachment on moist skin and use the memory contraction force to shrink the skin, improves mechanical properties and elasticity, enhances skin elasticity and improves wrinkles.
Smart Images

Figure CN120189344A_ABST
Abstract
Description
Technical Field
[0001] This specification discloses a film that has excellent mechanical properties, excellent stretchability, maintains a stretched state during stretching and drying, and when attached to wet skin, contracts the skin with a memorized contractile force. Background Art
[0002] In order to transmit a contractile force to the skin, an applicator is used or it is attached by pulling it oneself, so convenience is reduced or it is difficult to use with the same force each time. Conventional films attached to the skin have the drawback of losing adhesion in a wet environment. Summary of the Invention
[0003] In one aspect of the present disclosure, there is provided a film that has excellent mechanical properties, excellent stretchability, maintains a stretched state during stretching and drying, and when attached to wet skin, contracts the skin with a memorized contractile force.
[0004] In one aspect, the present disclosure provides a memory film, comprising: a first layer including acrylic acid and polyurethane, which contracts at a memory ratio after a lapse of time after being adhered to the skin.
[0005] In another aspect, the present disclosure provides a manufacturing method, as a manufacturing method of the aforementioned memory film, comprising: a step of coating and drying a solution including acrylic acid and polyurethane; and a step of stretching the coated and dried material.
[0006] In one aspect, the memory film according to the present disclosure has excellent mechanical properties and excellent stretchability, maintains a stretched state during stretching and drying, and when attached to wet skin, can contract the skin with a memorized contractile force. Brief Description of the Drawings
[0007] Figure 1 Shows the state in which the memory film according to an embodiment of the present disclosure contracts in a wet environment.
[0008] Figure 2 Is a photograph of observing the state of the skin as it contracts when the memory film according to an embodiment of the present disclosure is attached to the skin.
[0009] Figure 3 Is the result of comparing the physical properties of a double memory film or a single memory film according to an embodiment of the present disclosure. Detailed Description
[0010] Hereinafter, the present disclosure will be described more specifically by the following examples. However, the following examples are provided for illustrative purposes only to assist in understanding the present disclosure, and the scope and range of the present disclosure are not limited thereby.
[0011] In an exemplary instance of the present disclosure, a memory film is provided, comprising: a first layer including acrylic acid and polyurethane, which shrinks at a memory ratio after a period of time when adhered to the skin.
[0012] In an exemplary instance of the present disclosure, a method is provided for adhering a memory film including a first layer containing acrylic acid and polyurethane to the skin, which shrinks at a memory ratio after a period of time.
[0013] In an exemplary instance of the present disclosure, a use is provided of a first layer including acrylic acid and polyurethane for manufacturing a memory film that shrinks at a memory ratio after being adhered to the skin for a period of time.
[0014] In one instance, it can be that the memory film is used to enhance skin elasticity.
[0015] In one instance, it can be that the memory film is used to improve skin wrinkles.
[0016] In one instance, it can be that the memory film is used to increase skin density.
[0017] In one instance, it can be that the memory film is used to reduce one or more of pore depth, pore area, pore number, and pore volume.
[0018] In one instance, it can be that the time is from 1 hour to 24 hours.
[0019] For example, it can be that the time is more than 1 hour, more than 5 hours, more than 10 hours, more than 15 hours, or more than 20 hours, and is less than 24 hours, less than 20 hours, less than 15 hours, less than 10 hours, or less than 5 hours.
[0020] In one instance, it can be that the memory ratio is 100% with respect to the surface area after a period of time being 150% to 200% of the surface area when adhered to the skin.
[0021] For example, it can be that with respect to the surface area when adhered to the skin being more than 150%, more than 170%, or more than 190%, and less than 200%, less than 180%, or less than 160%, the surface area after a period of time is 100%.
[0022] In one instance, it can be that the acrylic acid is polyacrylic acid.
[0023] In one instance, it can be that the content of the polyurethane is less than 50% by weight based on the total weight of the first layer. When the polyurethane content is 50% by weight or more, the strength of the physical properties increases, but it returns to its original state during stretching and drying, and it may be difficult to be used as a memory film.
[0024] For example, the content of the polyurethane may be less than 50% by weight, less than 30% by weight, less than 20% by weight, less than 10% by weight, less than 5% by weight or less than 1% by weight based on the total weight of the first layer. For example, it may be 1% by weight or more, 5% by weight or more, 10% by weight or more, 20% by weight or more, 30% by weight or more or 40% by weight or more.
[0025] In one example, the weight ratio of the acrylic acid and the polyurethane may be from 1:1 to 3:1.
[0026] For example, the weight ratio of the acrylic acid and the polyurethane may be 1:1 or more, 1.5:1 or more, 2:1 or more or 2.5:1 or more, and 3:1 or less, 2.5:1 or less, 2:1 or less or 1.5:1 or less.
[0027] In one example, the first layer may further include Laponite. Laponite may be included to further improve the strength of the memory film.
[0028] The total molecular weight of the acrylic acid and the polyurethane may be from 100,000 to 1,000,000.
[0029] In this specification, the molecular weight is defined as the weight average molecular weight (Mw).
[0030] For example, the total molecular weight of the acrylic acid and the polyurethane may be 100,000 or more, 200,000 or more, 300,000 or more, 400,000 or more, 500,000 or more, 600,000 or more, 700,000 or more, 800,000 or more or 900,000 or more, and 1,000,000 or less, 900,000 or less, 800,000 or less, 700,000 or less, 600,000 or less, 500,000 or less, 400,000 or less, 300,000 or less or 200,000 or less.
[0031] In one example, the thickness of the first layer may be from 100 μm to 3000 μm.
[0032] For example, it may be that the thickness of the first layer is 100 μm or more, 300 μm or more, 500 μm or more, 700 μm or more, 900 μm or more, 1100 μm or more, 1300 μm or more, 1500 μm or more, 1700 μm or more, 2000 μm or more, or 2500 μm or more, and is 3000 μm or less, 2500 μm or less, 2000 μm or less, 1700 μm or less, 1500 μm or less, 1300 μm or less, 1100 μm or less, 900 μm or less, 700 μm or less, 500 μm or less, or 300 μm or less.
[0033] In one example, it may be that the memory film further includes: a second layer including one or more selected from the group consisting of polyurethane, spandex, PVC, and nylon. The memory film further includes a stretchable mesh or film such as polyurethane, spandex, PVC, or nylon as the second layer, thereby improving the physical properties and shrinkage strength of the memory film.
[0034] In one example, it may be that the second layer includes polyurethane.
[0035] For example, it may be that the second layer can be manufactured by coating a solution including polyurethane. It may be that the content of polyurethane in the solution is less than 50 wt%, less than 30 wt%, less than 20 wt%, less than 10 wt%, less than 5 wt%, or less than 1 wt% based on the total weight of the solution. For example, it may be 1 wt% or more, 5 wt% or more, 10 wt% or more, 20 wt% or more, 30 wt% or more, or 40 wt% or more.
[0036] For example, in the case of the finally manufactured second layer, the solvent in the solution can all volatilize and be composed of polyurethane.
[0037] In one example, it may be that the thickness of the second layer is 1 μm to 200 μm.
[0038] For example, it may be that the thickness of the second layer is 1 μm or more, 30 μm or more, 50 μm or more, 70 μm or more, 90 μm or more, 100 μm or more, 130 μm or more, 150 μm or more, or 170 μm or more, and is 200 μm or less, 170 μm or less, 150 μm or less, 130 μm or less, 100 μm or less, 90 μm or less, 70 μm or less, 50 μm or less, 30 μm or less, 10 μm or less, or 5 μm or less.
[0039] In yet another exemplary instance of the present disclosure, a manufacturing method is provided as the manufacturing method of the aforementioned memory film, including: a step of coating and drying a solution including acrylic acid and polyurethane; and a step of stretching the coated and dried material.
[0040] In one instance, it may be that the solution including the acrylic acid and polyurethane further includes lithium saponite.
[0041] In one instance, it may be that the solution including the acrylic acid and polyurethane further includes water and ethanol.
[0042] In one instance, before the step of coating and drying the solution including acrylic acid and polyurethane, a step of coating and drying a solution including one or more selected from the group consisting of polyurethane, spandex, PVC, and nylon is further included, so that a memory film further including a second layer can be manufactured.
[0043] In one instance, before the step of coating and drying the solution including acrylic acid and polyurethane, a step of coating and drying a solution including polyurethane is further included, so that a memory film further including a second layer can be manufactured.
[0044] For example, it may be that based on the total weight of the solution including the polyurethane, the content of the polyurethane is less than 50 wt.%, less than 30 wt.%, less than 20 wt.%, less than 10 wt.%, less than 5 wt.%, or less than 1 wt.%, and is 1 wt.% or more, 5 wt.% or more, 10 wt.% or more, 20 wt.% or more, 30 wt.% or more, or 40 wt.% or more.
[0045] In one instance, it may be that after the step of stretching, a step of drying is further included.
[0046] Hereinafter, the present invention will be described in more detail through examples. These examples are only for illustrating the present invention, and the scope of the present invention should not be construed as being limited by these examples, which will be obvious to those with ordinary knowledge in the technical field to which the present invention pertains.
[0047] Examples
[0048] Production Example 1. Production of a Single-Layer Memory Film
[0049] 1) Prepare Solution A.
[0050] - Dissolve 10 wt.% to 15 wt.% of polyurethane in a 95% ethanol solution.
[0051] 2) Prepare Solution B.
[0052] - A product obtained by dissolving saponite in an aqueous solution of 1 wt.% to 5 wt.% polyacrylic acid. The total molecular weight of polyacrylic acid and polyurethane is 800,000.
[0053] 3) Mix Solution A, Solution B, and 70% ethanol using a mixer. That is, produce a PU-PAA-saponite resin.
[0054] 4) Coating the uniformly mixed PU-PAA-saponite resin in step 3) with a thickness of 500 µm to 2000 µm and drying it uniformly.
[0055] 5) Conduct secondary heating and drying at a temperature of 100 °C or higher to initiate the cross-linking reaction caused by saponite.
[0056] 6) Hydrate the dried film, stretch it by 150% to 200%, and then completely dry it by heating.
[0057] Production Example 2. Production of a two-layer memory film (double film, Double patch)
[0058] 1) Prepare Solution A.
[0059] - Dissolve 10 wt.% to 15 wt.% polyurethane in a 95% ethanol solution.
[0060] 2) Coat Solution A with a thickness of 50 µm to 100 µm and dry it.
[0061] 3) Prepare Solution B.
[0062] - Dissolve saponite in a 1 wt.% to 5 wt.% polyacrylic acid solution.
[0063] 4) Mix Solution A, Solution B, and 70% ethanol using a mixer. That is, produce a PU-PAA-saponite resin.
[0064] 5) Coat the uniformly mixed PU-PAA-saponite resin in step 3) on the film dried from Solution A with a thickness of 500 µm to 2000 µm and dry it uniformly.
[0065] 6) Conduct secondary heating and drying at a temperature of 100 °C or higher to initiate the cross-linking reaction caused by saponite.
[0066] 7) Hydrate the dried film, stretch it by 150% to 200%, and then completely dry it by heating.
[0067] Test Example
[0068] Test Example 1 - Confirm shrinkage in a humid environment (providing strain)
[0069] AsFigure 1 As shown, when a moist environment (water) is provided to a stretched dry film (5 cm), a reduction in the film size (3.1 cm) was confirmed.
[0070] Test Example 2 - Facial shape change when attached to the skin
[0071] After applying an appropriate amount of water to the cheek area of the face and then applying a film with a size of 5 cm x 3 cm, as a result, through VECTRA H2FACE It was confirmed that after 5 minutes of application, the film shrank and changed the facial shape.
[0072] Refer to Figure 2 , it can be confirmed that compared with the left side of the face without the attached film, in the right side of the face with the attached film, the skin around the attached film gathered together.
[0073] Test Example 3 - Physical property comparison according to double or single film and molecular weight
[0074] Refer to Figure 3 , in the case of making a double film (double patch) with a total molecular weight of Mw = 800,000 of polyacrylic acid and polyurethane, the tensile strength (tensile property) is the highest. In the case of a single film (single patch), compared with the case where the total molecular weight (Mw) of polyacrylic acid and polyurethane is 250,000, in the case of 800,000, the tensile strength is significantly higher.
[0075] Test Example 4 - Evaluation of human efficacy for multiple items other than elasticity
[0076] Test product: Evaluate elasticity, lifting, wrinkles, skin density, and pores using the memory film manufactured in Manufacturing Example 1.
[0077] Test subjects: 25 women who met the selected criteria and did not meet the exclusion criteria [finally 20 completed the test, 47.200 ± 3.548 years old, 5 dropped out midway (did not follow the schedule)]
[0078] Test method: Before going to bed, attach the test product to the forehead & between the eyebrows and nasolabial folds on the face. About 8 hours after going to bed, gently remove it when washing the face in the morning. After continuous use for 7 days, before using the test product, 4 days after use, 7 days after use, and 21 days after interruption, device measurement and questionnaire evaluation were carried out.
[0079] * Before the start of the test, use the product once in the screening step and confirm adverse reactions. Use the personnel without adverse reactions as the subjects for this test
[0080] Evaluation items
[0081] 1) Equipment evaluation
[0082] - Elasticity: Cutometer
[0083] - Lifting: F-ray
[0084] - Wrinkles: Primos
[0085] - Skin density: Skin scanner
[0086] - Pores: Antera
[0087] 2) Subjective questionnaire evaluation based on the sense of use: Subjective questionnaire evaluation of the test subjects
[0088] 3) Safety evaluation: Adverse reaction evaluation of the test subjects
[0089] Test results
[0090] This test used women aged 40 to 53 with wrinkles and pores (those without surgical experience within 3 months) as subjects. In order to measure the improvement of multiple items other than elasticity, the test product was required to be used for 7 days, and equipment measurement and subjective questionnaire evaluation based on the sense of use were carried out. The following results were confirmed.
[0091] 1) Elasticity, R2
[0092] 1-1) Forehead
[0093] - As shown in Table 1 below, compared with before using the product, the elasticity measurement value was 10.000% after 4 days of use, 12.857% after 7 days of use, and 8.750% after 21 days of interruption. All increased at a significant level (p < 0.05), and it was confirmed that improvement was achieved.
[0094] [Table 1]
[0095]
[0096] *: p < 0.05 by paired samples t-test
[0097] ** : p < 0.05 by repeated measures ANOVA
[0098] Rate of change a (%) : [(Measured value after use - Measured value before use) / Measured value before use × 100]
[0099] Rate of change b (%) : [(Measured value after 21 days of interruption - Measured value before use) / Measured value before use × 100]
[0100] Rate of change c(%) : [(Measurement value after 21 days of interruption - Measurement value after 7 days of use) / Measurement value before use × 100]
[0101] 1 - 2) Cheek
[0102] - As shown in Table 2 below, compared with before using the product, the elasticity measurement values were 7.431% after 4 days of use, 9.370% after 7 days of use, and 7.916% after 21 days of interruption, all increased at a significant level (p < 0.05), and improvement was confirmed.
[0103] - The elasticity measurement value after 21 days of interruption did not show a significant difference from that after 7 days of use (p > 0.05), and the elasticity retention effect was confirmed until 21 days after interruption of use.
[0104] [Table 2]
[0105]
[0106] ## : p < 0.025 (= 0.05 / 2), post - hoc test analysis was performed by Friedman test and paired Wilcoxon signed - rank test using Bonferroni correction
[0107] Rate of change a (%) : [(Measurement value after use - Measurement value before use) / Measurement value before use × 100]
[0108] Rate of change b (%) : [(Measurement value after 21 days of interruption - Measurement value before use) / Measurement value before use × 100]
[0109] Rate of change c (%) : [(Measurement value after 21 days of interruption - Measurement value after 7 days of use) / Measurement value before use × 100]
[0110] 2) Lifting, °
[0111] - As shown in Table 3 below, compared with before using the product, the lifting measurement values were 1.508% after 4 days of use, 2.364% after 7 days of use, and 0.724% after 21 days of interruption, all increased at a significant level (p < 0.05), and improvement was confirmed.
[0112] [Table 3]
[0113]
[0114] * : p < 0.05 by paired - samples t - test
[0115] ** : p < 0.05 by repeated - measures ANOVA
[0116] Rate of change a (%) : [(Measured value after use - Measured value before use) / Measured value before use × 100]
[0117] Rate of change b (%) : [(Measured value 21 days after interruption - Measured value before use) / Measured value before use × 100]
[0118] Rate of change c (%) : [(Measured value 21 days after interruption - Measured value 7 days after use) / Measured value before use × 100]
[0119] 3) Wrinkles, Ra
[0120] 3-1) Forehead
[0121] - As shown in Table 4 below, compared with before using the product, the measured value of wrinkles was 7.968% after 4 days of use, and it decreased at a significant level (p < 0.05), confirming that improvement was achieved.
[0122] [Table 4]
[0123]
[0124] ## : p < 0.025 (= 0.05 / 2), post hoc test analysis was performed by Friedman test and paired Wilcoxon signed-rank test using Bonferroni correction
[0125] Rate of change a (%) : [(Measured value after use - Measured value before use) / Measured value before use × 100]
[0126] Rate of change b (%) : [(Measured value 21 days after interruption - Measured value before use) / Measured value before use × 100]
[0127] Rate of change c (%) : [(Measured value 21 days after interruption - Measured value 7 days after use) / Measured value before use × 100]
[0128] 3-2) Between eyebrows
[0129] - As shown in Table 5 below, compared with before using the product, the measured value of wrinkles was 5.682% after 4 days of use, and it decreased at a significant level (p < 0.05), confirming that improvement was achieved.
[0130] [Table 5]
[0131]
[0132] *: p < 0.05 by paired-samples t-test
[0133] ** : p < 0.05 by repeated measures ANOVA
[0134] Rate of change a (%) : [(Measured value after use - Measured value before use) / Measured value before use × 100]
[0135] Rate of change b (%) : [(Measured value 21 days after interruption - Measured value before use) / Measured value before use × 100]
[0136] Rate of change c (%) : [(Measured value 21 days after interruption - Measured value 7 days after use) / Measured value before use × 100]
[0137] 3-3) Nasolabial folds
[0138] - As shown in Table 6 below, compared with before product use, the wrinkle measurement value decreased by 2.907% after 4 days of use and by 3.160% after 7 days of use, and improvement was confirmed at a significance level (p < 0.05).
[0139] [Table 6]
[0140]
[0141] * : p < 0.05 by paired-samples t-test
[0142] ** : p < 0.05 by repeated measures ANOVA
[0143] Rate of change a (%) : [(Measured value after use - Measured value before use) / Measured value before use × 100]
[0144] Rate of change b (%) : [(Measured value 21 days after interruption - Measured value before use) / Measured value before use × 100]
[0145] Rate of change c (%) : [(Measured value 21 days after interruption - Measured value 7 days after use) / Measured value before use × 100]
[0146] 4) Skin denseness, %
[0147] 4-1) Forehead
[0148] - As shown in Table 7 below, compared with before using the product, the skin density measurement value increased at a significance level (p < 0.05) to 5.028% after 4 days of use and 4.470% after 7 days of use, and improvement was confirmed.
[0149] [Table 7]
[0150]
[0151] * : p < 0.05 by paired samples t-test
[0152] ** : p < 0.05 by repeated measures ANOVA
[0153] Rate of change a (%) : [(Measured value after use - Measured value before use) / Measured value before use × 100]
[0154] Rate of change b (%) : [(Measured value after 21 days of interruption - Measured value before use) / Measured value before use × 100]
[0155] Rate of change c (%) : [(Measured value after 21 days of interruption - Measured value after 7 days of use) / Measured value before use × 100]
[0156] 4 - 2) Cheek
[0157] - As shown in Table 8 below, compared with before using the product, the skin density measurement value increased at a significance level (p < 0.05) to 7.508% after 4 days of use and 7.606% after 7 days of use, and improvement was confirmed.
[0158] [Table 8]
[0159]
[0160] * : p < 0.05 by paired samples t-test
[0161] ** : p < 0.05 by repeated measures ANOVA
[0162] Rate of change a (%) : [(Measured value after use - Measured value before use) / Measured value before use × 100]
[0163] Rate of change b (%) : [(Measured value after 21 days of interruption - Measured value before use) / Measured value before use × 100]
[0164] Rate of change c(%) : [(Value measured 21 days after interruption - Value measured 7 days after use) / Value measured before use × 100]
[0165] 5) Pores
[0166] 5-1) Pore depth, mm
[0167] - As shown in Table 9 below, compared with before using the product, the measured value of pore depth was 10.000% 7 days after use, and decreased at a significant level (p < 0.05), indicating that improvement was confirmed.
[0168] [Table 9]
[0169]
[0170] # : p < 0.05 by Wilcoxon signed-rank test
[0171] ## : p < 0.025 (= 0.05 / 2) by Friedman test and post hoc test analysis using paired Wilcoxon signed-rank test with Bonferroni correction
[0172] Rate of change a (%) : [(Value measured after use - Value measured before use) / Value measured before use × 100]
[0173] Rate of change b (%) : [(Value measured 21 days after interruption - Value measured before use) / Value measured before use × 100]
[0174] Rate of change c (%) : [(Value measured 21 days after interruption - Value measured 7 days after use) / Value measured before use × 100]
[0175] 5-2) Pore area, mm 2
[0176] - As shown in Table 10 below, compared with before using the product, the measured value of pore area was 15.198% 4 days after use, 20.629% 7 days after use, and 10.172% 21 days after interruption, all of which decreased at a significant level (p < 0.05), indicating that improvement was confirmed.
[0177] [Table 10]
[0178]
[0179] # : p < 0.05 by Wilcoxon signed-rank test
[0180] ##: p < 0.025 (= 0.05 / 2), post - hoc test analysis was performed by the Friedman test and paired Wilcoxon signed - rank test with Bonferroni correction
[0181] Rate of change a (%) : [(Measured value after use - Measured value before use) / Measured value before use × 100]
[0182] Rate of change b (%) : [(Measured value 21 days after interruption - Measured value before use) / Measured value before use × 100]
[0183] Rate of change c (%) : [(Measured value 21 days after interruption - Measured value 7 days after use) / Measured value before use × 100]
[0184] 5 - 3) Number of pores, ea
[0185] - As shown in Table 11 below, compared with before using the product, the measured value of the number of pores was 10.109% after 4 days of use, 14.412% after 7 days of use, and 5.236% 21 days after interruption, all of which decreased at a significant level (p < 0.05), and improvement was confirmed
[0186] [Table 11]
[0187]
[0188] * : p < 0.05 by paired - samples t - test
[0189] ** : p < 0.05 by repeated - measures ANOVA
[0190] Rate of change a (%) : [(Measured value after use - Measured value before use) / Measured value before use × 100]
[0191] Rate of change b (%) : [(Measured value 21 days after interruption - Measured value before use) / Measured value before use × 100]
[0192] Rate of change c (%) : [(Measured value 21 days after interruption - Measured value 7 days after use) / Measured value before use × 100]
[0193] 5 - 4) Pore volume, mm 3
[0194] - As shown in Table 12 below, compared with before using the product, the measured value of pore volume decreased by 16.517% after 4 days of use, 22.823% after 7 days of use, and 12.012% after 21 days of interruption, all of which decreased at a significant level (p < 0.05), and improvement was confirmed.
[0195] [Table 12]
[0196]
[0197] # : p < 0.05 by Wilcoxon signed-rank test
[0198] ## : p < 0.025 (= 0.05 / 2) by Friedman test and post hoc test analysis using paired Wilcoxon signed-rank test with Bonferroni correction
[0199] Rate of change a (%) : [(Measured value after use - Measured value before use) / Measured value before use × 100]
[0200] Rate of change b (%) : [(Measured value after 21 days of interruption - Measured value before use) / Measured value before use × 100]
[0201] Rate of change c (%) : [(Measured value after 21 days of interruption - Measured value after 7 days of use) / Measured value before use × 100]
[0202] 6) Results of subjective questionnaire evaluation based on usability
[0203] - The results of subjective questionnaire evaluation based on usability after using the test product are as shown in the following table.
[0204] [Table 13]
[0205] [Questionnaire evaluation after 4 days of use]
[0206]
[0207] [Table 14]
[0208] [Questionnaire evaluation after 7 days of use]
[0209]
[0210] [Table 15]
[0211] [Questionnaire evaluation after 21 days of use]
[0212]
[0213] 7) Safety
[0214] There were no reports of specific adverse reactions during the use of the test product by the test subjects. Therefore, the product was judged to be safe.
[0215] In summary, it was judged that the patch according to this embodiment was helpful for improving elasticity (forehead, cheeks), lifting, wrinkles (forehead, glabella, nasolabial folds), skin density (forehead, cheeks), and pores (area, number, volume) after 4 days of use, and was judged to be helpful for improving elasticity (forehead, cheeks), lifting, wrinkles (nasolabial folds), density (forehead, cheeks), and pores (depth, area, number, volume) after 7 days of use.
[0216] In addition, it was judged that, compared with before use, after 7 days of use and 21 days after discontinuation of use, it was helpful for improving elasticity (forehead, cheeks), lifting, and pores (area, number, volume), and was judged to be helpful for maintaining the improvement of elasticity (cheeks) from 7 days of use to 21 days after discontinuation.
[0217] Specific examples
[0218] Specific example 1: A memory film, comprising a first layer including acrylic acid and polyurethane, which shrinks at a memory ratio after a period of time after being adhered to the skin.
[0219] Specific example 2: In the memory film of specific example 1, the memory film is used to enhance skin elasticity.
[0220] Specific example 3: In the memory film of specific example 1 or 2, the memory film is used to improve skin wrinkles.
[0221] Specific example 4: In the memory film according to any one of specific examples 1 to 3, the memory film is used to increase skin density.
[0222] Specific example 5: In the memory film according to any one of specific examples 1 to 4, the memory film is used to reduce one or more of pore depth, pore area, pore number, and pore volume.
[0223] Specific example 6: In the memory film according to any one of specific examples 1 to 5, the time is 1 to 24 hours.
[0224] Specific example 7: In the memory film according to any one of specific examples 1 to 6, the memory ratio is 100% with respect to the surface area after a period of time being 150%-200% of the surface area when adhered to the skin.
[0225] Specific example 8: In the memory film according to any one of specific examples 1 to 7, the acrylic acid is polyacrylic acid.
[0226] Specific Example 9: In the memory film according to any one of Specific Examples 1 to 8, the content of the polyurethane is less than 50% by weight based on the total weight of the first layer.
[0227] Specific Example 10: In the memory film according to any one of Specific Examples 1 to 9, the weight ratio of the acrylic acid and the polyurethane is 1:1 to 3:1.
[0228] Specific Example 11: In the memory film according to any one of Specific Examples 1 to 10, the first layer further includes Laponite.
[0229] Specific Example 12: In the memory film according to any one of Specific Examples 1 to 11, the total molecular weight of the acrylic acid and the polyurethane is 100,000 to 1,000,000.
[0230] Specific Example 13: In the memory film according to any one of Specific Examples 1 to 12, the thickness of the first layer is 100 μm to 1500 μm.
[0231] Specific Example 14: In the memory film according to any one of Specific Examples 1 to 13, the memory film further includes: a second layer including one or more selected from the group consisting of polyurethane, spandex, PVC, and nylon.
[0232] Specific Example 15: In the memory film according to any one of Specific Examples 1 to 14, the second layer includes polyurethane.
[0233] Specific Example 16: In the memory film according to any one of Specific Examples 1 to 15, the thickness of the second layer is 1 μm to 100 μm.
[0234] Specific Example 17: A use, as the use of the memory film according to any one of Specific Examples 1 to 16, the use is for enhancing skin elasticity; improving skin wrinkles; increasing skin density; or reducing one or more of pore depth, pore area, pore number, and pore volume.
[0235] Specific Example 18: A manufacturing method, as the manufacturing method of the memory film according to any one of Specific Examples 1 to 16, includes: a step of coating and drying a solution including acrylic acid and polyurethane; and a step of stretching the coated and dried material.
[0236] Specific Example 19: In the manufacturing method of Specific Example 18, the solution including the acrylic acid and the polyurethane further includes Laponite.
[0237] Specific Example 20: In the manufacturing method of Specific Example 18 or 19, the solution including the acrylic acid and the polyurethane further includes water and ethanol.
[0238] Specific Example 21: In the manufacturing method according to any one of Specific Examples 18 to 20, after the stretching step, a drying step is further included.
Claims
1. A memory film, comprising: The first layer, including acrylic and polyurethane, After bonding to the skin, it shrinks at a memory ratio over time.
2. The memory film according to claim 1, wherein: The memory film is used to enhance skin elasticity.
3. The memory film according to claim 1, wherein: The memory film is used for improving skin wrinkles.
4. The memory film according to claim 1, wherein: The memory film is used to increase skin density.
5. The memory film according to claim 1, wherein: The memory film is used to reduce at least one of pore depth, pore area, pore number and pore volume.
6. The memory film according to claim 1, wherein: The time is 1 hour to 24 hours.
7. The memory film according to claim 1, wherein: The memory ratio is 100% of the surface area after the passage of time relative to 150% to 200% of the surface area when adhering to the skin.
8. The memory film according to claim 1, wherein: The acrylic acid is polyacrylic acid.
9. The memory film according to claim 1, wherein: The content of the polyurethane is less than 50 wt % based on the total weight of the first layer.
10. The memory film according to claim 1, wherein: The weight ratio of the acrylic acid to the polyurethane is 1:1 to 3:
1.
11. The memory film according to claim 1, wherein: The first layer also includes laponite.
12. The memory film according to claim 1, wherein: The total molecular weight of the acrylic acid and the polyurethane is 100,000 to 1,000,000.
13. The memory film according to claim 1, wherein: The thickness of the first layer is 100 μm to 3000 μm.
14. The memory film according to claim 1, wherein: The memory film also includes: The second layer includes at least one selected from the group consisting of polyurethane, spandex, PVC and nylon.
15. The memory film according to claim 14, wherein: The second layer includes polyurethane.
16. The memory film according to claim 14, wherein: The thickness of the second layer is 1 μm to 200 μm.
17. Use of a memory film, wherein the memory film is the memory film according to any one of claims 1 to 16, The uses are: to enhance skin elasticity; to improve skin wrinkles; to increase skin density; or to reduce one or more of pore depth, pore area, pore number and pore volume.
18. A method for manufacturing a memory film, wherein the memory film is the memory film according to any one of claims 1 to 16, the method comprising: The steps of applying and drying a solution including acrylic acid and polyurethane; as well as The coated and dried material is subjected to a stretching step.
19. The manufacturing method according to claim 18, wherein: The solution including the acrylic acid and the polyurethane further includes laponite.
20. The manufacturing method according to claim 18, wherein: The solution including the acrylic acid and the polyurethane further includes water and ethanol.
21. The manufacturing method according to claim 18, wherein: The manufacturing method further comprises a drying step after the stretching step.